Proof. We shall prove only the first of these statements
leaving the other statements as exercises. Take any square
matrix A of order n.
Let B be the matrix such that B(i,j)=A(i,j) if i is greater than j
and B(i,j)=0 otherwise (i,j=1,2,...,n).
Let C be A-B. Then B is an upper triangular
matrix by definition. The matrix C is
lower triangular because for every i and j if i is greater than j then
C(i,j)=A(i,j)-B(i,j)=A(i,j)-A(i,j)=0
(We used the definition of B, namely the fact that B(i,j)=A(i,j) if i
is greater than j.)